Avaliação da ocorrência sazonal de percevejos em cinco espécies de maracujazeiro, utilizando dois métodos de amostragem - Caetano, Antonio Cesar [UNESP]; BOIÇA JÚNIOR, ARLINDO LEAL [UNESP]; RUGGIERO, CARLOS [UNESP] (Instituto Agronômico de Campinas, 2000)
O presente trabalho teve por objetivo estudar a ocorrência sazonal de percevejos em espécies de maracujazeiro (Passiflora spp.) através de dois métodos de amostragem: número de percevejos por 0,5 m² e em 1,5 m linear de espaldeira. O experimento foi conduzido em pomar de maracujazeiro pertencente à Faculdade de Ciências Agrárias e Veterinárias - UNESP, Jaboticabal, Estado de São Paulo, entre setembro de 1997 e setembro de 1998. Foram utilizadas cinco espécies de maracujazeiro: P. alata, P. edulis f. flavicarpa, P. nitida, P. giberti e P. laurifolia. Após as avaliações semanais pôde-se concluir que as espécies de percevejo Leptoglossus gonagra, L. zonatus, Holhymenia histrio e Anisoscelis foliacea marginella foram as mais abundantes em maracujazeiro. L. gonagra, H. histrio e A. foliacea marginella apresentaram maiores populações entre o final de dezembro e início de maio e L. zonatus ocorreu em maior população entre o final de março e o de julho. O método de 0,5 m² foi o mais adequado para avaliação de percevejos. P. laurifolia foi mais atrativo para L. gonagra, P. edulis f. flavicarpa mais atrativo para L. zonatus e P. giberti para A. foliacea marginella e H. histrio.

Stinkbug population dynamics has been studying in passion fruit (Passiflora spp.) under field conditions in Jaboticabal, São Paulo State. Two sampling methods have been utilized: a) countings of the number of insects occurring in a 0.5 m² wooden frame; b) countings of the number of insects present in 1.5 linear meter, aside of a tutoring system. Five passion fruit species (Passiflora alata, P. edulis f. flavicarpa, P. nitida, P. giberti and P. laurifolia) have been checked as to insect occurrence throughout a year. Weekly, insect samples have been collected in 5 randomly choosen sites in the orchard, for each evolution method.The most frequent stinkbug species, considering all the passion fruit species, have been the following: Leptoglossus gonagra, L. zonatus, Holhymenia histrio and Anisoscelis foliacea marginella; the highest populations for L. gonagra, H. histrio and A. foliacea marginella have occurred from late December to early May while those of L. zonatus revealed the highest numbers from late March to late July. P. laurifolia has been the most attractive species to L. gonagra; P. edulis f. flavicarpa to L. zonatus; P. giberti to A. foliacea marginella and H. histrio.The sampling method using a 0.5 m² wooden frame has shown to be the most effective as to population dynamics evolutions.
Evaluation of seasonal stinkbug occurrence in five passion fruit species using two sampling methods
Keywords: Passiflora spp.; Coreidae; Leptoglossus; Holhymenia; Anisoscelis; Passiflora spp.; Coreidae; Leptoglossus; Holhymenia; Anisoscelis